Penerapan Teknik Stop Motion dalam Pembelajaran Subnetting Variable Length Subnetmask Berbasis Multimedia - Sahal Lubis, Muhammad; Sundari, Siti; Dharmawati, Dharmawati (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2024)
This research aims to explore the application of stop motion technique in teaching subnetting with Variable Length Subnet Mask (VLSM) through multimedia-based learning. Subnetting, particularly with VLSM, is often perceived as a complex and challenging topic for students in the field of computer networking. Thus, this study focuses on the development and evaluation of instructional materials that use stop motion technique to visually and interactively explain subnetting concepts. The methodology involves designing and creating stop motion videos that illustrate the steps of subnetting with VLSM. These videos are then integrated into a multimedia learning module accessible to students. The effectiveness of using stop motion videos in enhancing students' understanding and skills in subnetting is evaluated through case studies and surveys. The results indicate that the use of stop motion technique significantly facilitates clearer and more engaging comprehension of subnetting with VLSM. Students exposed to multimedia learning materials with stop motion technique demonstrate a notable improvement in their understanding and application of subnetting compared to traditional methods. The study concludes that stop motion is an effective tool in teaching networking techniques, positively impacting student engagement and learning outcomes.Keywords: stop motion, subnetting, Variable Length Subnet Mask (VLSM), multimedia learning